1998
DOI: 10.1021/ma9714225
|View full text |Cite
|
Sign up to set email alerts
|

Random Polybutadiene Rubber Networks with Unattached Chains

Abstract: The preparation and characterization of randomly cross-linked polybutadiene (PB) networks containing unattached PB chains are presented. These were used as model systems for the experimental study of the dynamics of linear chains trapped in networks, which is the basic model of the reptationin-a-tube model of Doi and Edwards. The preparation consists of the conversion at random of a small fraction of the PB chains' double bonds into epoxide groups and in the subsequent selective use of these as cross-linking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…! ÿ1=2 high frequency slope [20,21], in agreement with the prediction of the original reptation theory [5]. Moreover, the angular frequency position of the G 00 peak, !…”
supporting
confidence: 84%
“…! ÿ1=2 high frequency slope [20,21], in agreement with the prediction of the original reptation theory [5]. Moreover, the angular frequency position of the G 00 peak, !…”
supporting
confidence: 84%
“…This may have depended on the difference in the distances between lignin particles in the ENR matrix and the effective thickness of the lignin–ENR matrix interphase, namely, whether the motion of all of the polymer chain segments could be restricted by fillers . If all of the polymer chains were crosslinked by lignin, the translational flow and disentanglement flow of polymer chains will be prevented; this remarkably improved the T g of the polymer compared to that of an incompletely crosslinked one . Therefore, we could reasonably deduce that the ENR molecules of the SLEs with the inclusion of more than 10‐phr lignin were completely crosslinked; this could form homogeneous networks to transfer external stress.…”
Section: Resultsmentioning
confidence: 95%
“…30 If all of the polymer chains were crosslinked by lignin, the translational flow and disentanglement flow of polymer chains will be prevented; this remarkably improved the T g of the polymer compared to that of an incompletely crosslinked one. 31 Therefore, we could reasonably deduce that the ENR molecules of the SLEs with the inclusion of more than 10-phr lignin were completely crosslinked; this could form homogeneous networks to transfer external stress. No obvious variation in T g of SLE10 compared with that of pure ENR indicated that not all of the chain segments of ENR could be restricted by lignin via covalent bonding.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 83%
“…Ndoni et al showed that the dependence of τ on the molecular size of the unattached PB was well explained by the tube model considering contour length fluctuation of tube. 17 The dielectric normal mode relaxation measurement using the cis-polyisoprene (PI) (with the Stockmayer's type-A dipoles parallel to the chain contour) is one of the most straightforward techniques to pick up the signal solely from the guest chain. On the basis of the dielectric normal mode relaxation measurements for cis-PI trapped in a cross-linked PB network, Adachi et al 13 reported the fairly stronger dependence of τ on the molecular size of guest chain relative to the cubic power law by the original tube model.…”
Section: Introductionmentioning
confidence: 99%